Associations Among Attention Problems, Learning Strategies, and Hazardous Drinking Behavior in a College Student Sample: A Pilot Study. (May 2019) - Bolden, Jennifer
Despite research linking substance use/abuse to pejorative academic outcomes, the underlying behavior and cognitive mechanisms responsible for this association are largely unknown. This study addresses a specific call for understanding learning strategies and skills associated with substance alcohol use/abuse. Four hundred fifty undergraduates (59.6% female) completed measures of hazardous drinking behavior and student learning strategies. Approximately 35.3% of the sample reported hazardous drinking scores in the clinical range. Bivariate correlations and a regression framework were utilized to understand the associations among hazardous drinking behavior, academic skills/strategies, and student liabilities. In the present study, hazardous drinking behavior was associated with 4 learning strategies: note-taking/listening skills, test-taking strategies, organizational techniques, and time management. Moreover, hazardous drinking behavior was associated with 2 student liabilities: low academic motivation and concentration/attention difficulties. Results from follow-up analyses suggest that only organizational techniques and concentration/attention difficulties predicted hazardous drinking behavior. Promising areas for future research and potential intervention targets are discussed.